KIERKEGAARD’S EXISTENTIALISM ON THE MAIN CHARACTER IN PAULO COELHO’S THE ZAHIR - Asy’ari, Asharuddin; Andayani, Ambar (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
This study aims to discuss the issue of Existentialism in Coelho’s The Zahir. The objectives of this study are to analyze the existentialism exposed in the novel on the main character of the novel. This study uses descriptive qualitative method using philosophical approach and several theories of existentialism. The result of this study shows that the novel depicts the existentialism in the main character of the novel based on elements, stages of the existentialism and the subjectivity of the truth of main character. The elements are: despair and anxiety. The stages are: the aesthetic, ethical and religious stage. The subjective truth is defined as the way of person meaning a truth. The Concept of Anxiety in Relation with Ethical Stage. Despair is indicated when the character feels hopeless and soulless, anxiety is depicted when the character feels anxious without reason. In addition, the aesthetic stage is portrayed when the character acts selfish and arrogant, the ethical is described when the character becomes aware of the human nature, and the religious stage is shown when the character believes in god. The subjective truth is explained that the truth comes from the individual